Survey on the Pharmaceutical Quality of Herbal Medicines Sold in Nigeria - Philip F. Builders, Chris A. Alalor, John A. Avbunudiogba, Isreal E. Justice (Journal of Applied Pharmaceutical Science, 2015)
In recent times the apparent upsurge in the popularity and use of herbal medicines can be related to the success in their use for the management of certain important diseases, empirical proof of efficacy and safety, enhanced dosage form design and better tolerance among others. In this study the quality of some herbal medicines sold in Nigeria were evaluated for basic pharmaceutical quality and compliance to regulatory guidelines. Samples of sixteen frequently used herbal products were collected from Pharmacy stores (Ps) and Patent Medicine stores (PMs) across two states and the Federal Capital Territory. The dosage form, organoleptic properties, moisture content, weight/volume uniformity as well as compliance to regulatory guidelines were evaluated. Sixty percent of the samples were liquids, thirty percent were oral bulk powders and ten percent were capsules. None of the products complied completely with the regulatory requirement stipulated for finished herbal products in Nigeria while only ten percent of the products samples complied with the basic physicochemical properties required for pharmaceutical quality. Consequently, there is a compelling need for the regulatory authorities to ensure stringent quality surveillance and enforcement of guidelines to ensure that herbal medicines are of standard quality.
Keywords: Herbal medicine, regulatory guidelines, pharmaceutical quality.